Improving Energy Saving in Conventional Pneumatic Systems by Using Air Booster Experimentally - Jafar Mehdi Hassan; Majid Ahmed Oleiwi; Amer Abed Mansour; Walaa Mousa Hashim (Engineering and Technology Journal, 2015)
Pneumatic actuators are widely used in industry and many other applications, whereas low energy efficiency has been recognized as a critical drawback compared with corresponding hydraulic and electrical actuators. The paper presents a study to improve the performance and energy efficiency of the traditional pneumatic drive with vertical load 50N, by added air booster type IPR (Input Pressure Reduce) to the.Four supply pressures used 2, 4, 6 and 8 bar, compared with the traditional control of the motion of the asymmetric cylinder in which maximum energy saving obtained at 6 bar16.7%.